PROFESSIONAL ETHICS OF ISLAMIC RELIGIOUS EDUCATION (PAI) TEACHERS IN THE UTILIZATION OF LEARNING TECHNOLOGY IN THE DIGITAL ERA AT SMPN 8 PAMEKASAN - Nurul Ain Astutik; Norma Kumala Sari; Mamluatul Ilmiyeh; Fitria; Abd Mukhid (SOSIOEDUKASI, 2026)
Advancements in the digital age require teachers of Islamic Religious Education (PAI) to adopt contemporary educational technologies while preserving professional ethics grounded in Islamic pedagogical values, despite issues such as misuse of digital content and diminished interpersonal connections, evident at SMPN 8 Pamekasan. This study examines ethical frameworks for PAI educators from an Islamic perspective, evaluates the function of technology in contemporary teaching practices, identifies ethical guidelines for its implementation, and investigates challenges and impacts on primary-level education. Employing a qualitative approach with a literature-based methodology, this research reviews classical Islamic sources (including works by Al-Ghazali and Ibn Qayyim), contemporary academic journals on education, and Indonesian national policies pertaining to PAI teacher ethics in elementary schools. The study focuses on PAI instructors within the context of Indonesia's primary education system, utilizing SMPN 8 Pamekasan as a representative example. The collected data undergoes descriptive-critical analysis to produce comprehensive findings.